Mythical Aspects of the Cane of Moses in Persian Exegeses - Mousavi Kahani, Zahra (2021)
The stories and parables that we see in Quran have a logical course but our Persian exegetical texts are full of appendices which have become combined with myth. In Quran, the word “myths” is of a negative content but the reality is that human mind tends to add to the significance of the event by exaggeration and empowerment of the persons and objects. The story of Moses in Quran is one of the most extensive stories and his cane is capable of turning to a mythical symbol. Thus, this essay studies the mythocentric approach of it in four Persian exegeses.